SPELLING ERRORS IN ACADEMIC PAPERS WRITTEN BY STUDENTS OF THE INFORMATICS STUDY PROGRAM AT UNIVERSITAS PERWIRA PURBALINGGA - Almas Rifqi Darmawan; Melia Dwi Renovriska; Lukman Maulana (Journal of Language, Literature and Teaching, 2026)
The application of linguistic rules is essential in academic writing and should receive serious attention in higher education. Indonesian is one of the compulsory university courses intended to help students apply proper language rules in academic texts. However, many students still experience difficulties in using correct spelling in their academic writing. These problems are often influenced by limited understanding of Indonesian spelling rules and low interest in learning them. This study aimed to examine spelling errors found in students’ academic writing. It employed a qualitative approach with a descriptive design and used content analysis as the main method, focusing on students’ academic texts. The data were obtained from both primary and secondary sources. The primary data consisted of papers written by second-semester students in the Informatics Study Program at Universitas Perwira Purbalingga, while the secondary data included theoretical books from the National Library and relevant scholarly publications available online. The findings showed that students still made errors in the use of capital letters, italics, punctuation marks, prefixes, prepositions, standard words, and word combinations. These results indicate that Indonesian language courses play an important role in improving the quality of students’ academic writing, especially in preparing them for undergraduate thesis writing.